Pengaruh Good Corporate Governance, Manajemen Risiko dan Financing to Deposit Ratio terhadap Kinerja Keuangan Bank Umum Syariah - Sofyan Halim; Mohammad Torik Langlang Buana (Neolectura, 2022)
The research aims to review the Financial Performance of Islamic Commercial Bank Entities with independent variables of good corporate governance through an analysis of the composition of the Independent Commissioner Structure and Institutional Ownership, risk management analysis and financing to deposit review. This research is a quantitative method so that it can analyze the causal relationship between the research variables following the hypotheses formulated. The hypothesis designed, namely regarding the effect of independent variable (GCG, NPF, FDR) on the ROA as dependent variable the results of the study concluding that the Structure of the Board of Commissioners as part of the implementation of GCG has a positive effect on the performance of the entity (ROA), while the performance of the Entity (ROA) is negatively influenced by Institutional Ownership as part of the implementation of GCG, as well as the Return on Asset is not significantly affected by non-profit Performing Financing (NPF), as well as ROA are positively affected by the Financing to Deposit Ratio.Based on the results of adjusted R Square analysis of 37.72%, so this is a limitation of this study, and it shows that other factors outside the research model of 62.28% are needed for further research with different variables and research periods, so that research on this study becomes more perfect.